Persepsi Masyarakat Desa Wangkelang terhadap Budaya Perawatan Ibu Postpartum - Dwi Lemintu Ningsih; Lutfatul Latifah; Meivita Dewi Purnamasari (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
Background: The postpartum period is critical in the survival of mothers and newborns. Postpartum care can be done traditionally. The culture of postpartum care is very diverse; the perception of the community itself influences the application of postpartum care culture. Aim: This study aims to determine the public perception of the culture of postpartum maternal care. Methods: This study uses a qualitative method with a descriptive approach. There were six informants in this study, the informants were mothers who had given birth. This study uses data analysis steps: data reduction, categorization, synthesis, and hypothesis. Results: This study yielded three themes (types of culture, cultural perception, and preserving culture). Several existing treatment cultures range from dietary restrictions, behavior, dress, food recommendations, dressing, and traveling. In addition, there is a culture that is not following health, and there are also negative and positive impacts of culture so that some people have the perception to preserve it. The culture of postpartum mother care in Wangkelang village is very diverse. However, some cultures are not following health science. Apart from that, there are also positive and negative impacts of culture. Culture is a legacy and a habit that is carried out continuously. Conclusion: There are many cultures of caring for postpartum mothers in Wangkelang Village, such as food restrictions, activity restrictions, dress restrictions and travel restrictions.